Taxonomy of common taxa of Chlorophyceae (Chlorophyta) and Zygnematophyceae (Streptophyta) from periphyton of a Neotropical floodplain - Stefania Biolo; Vanessa Majewski Algarte; Liliana Rodrigues (Acta Scientiarum. Biological Sciences, 2020)
Some orders of algal groups such as Chlorophyceae and Zygnematophyceae have been reported as frequent taxa in periphytic communities of wetlands. The present study aimed at submitting these algal members which occurred in high abundance and frequency in the periphyton of 30 environments of the Upper Paraná River floodplain to a taxonomic survey and to present some ecological data concerning their richness. Periphyton were collected from petioles by scraping of Eichhornia azurea (Sw.) Kunth and preserved with Lugol acetic solution in the Upper Paraná River, Brazil, during high water period in March 2010. Taxa were counted in inverted microscope and those higher than 2,500 individuals in density with frequency of occurrence less than 50% simultaneously in the 30 environments sampled were subjected to a detailed taxonomical treatment under optical microscope coupled to a light camera and ocular micrometer under 1000x. Identifications and descriptions were made according to the algal literature. Some abiotic data were shown. Fifteen taxa belonging to the classes Chlorophyceae and Zygnematophyceae were abundant representing 64.6% of the total density. A Procruste analysis within a Detrended Correspondence Analysis showed that distribution pattern of richness of clorophyceans and zygnematophyceans was represented by common species of these communities, highlighting the importance of knowing about these algae taxonomy